Seagrass traits (ramet level) in Unguja Island (Zanzibar Archipealgo, Tanzania) sampled in 2016 - Agustín Moreira-Saporiti; Mirta Teichberg (PANGAEA, 2021)
We studied if functional traits related to resource preemption (light and inorganic nutrients) exert control on space preemption of tropical seagrass meadows. Additionally, we studied if space preemption changed under different eutrophication scenarios. We took seagrass abundance data to study space preemption, seagrass traits data to study their effect on space preemption and eutrophication indicators to evaluate the level of eutrophication at each site/sampling event. The data was collected in Unguja Island (Zanzibar Archipealgo, Tanzania) in seven sites/sampling events (Harbor, Chapwani, Changuu, Bweleo, Fumba, Mangroves and Marumbi). Each site/sampling event comprised a subtidal seagrass meadow (2-4 meters depth) of around 2500 square meters, delimited by the coastline and a fringing reef. The data was taken between the 26.09.2016 to the 05.10.2016. In each site/sampling event, five 50 meters transects were deployed perpendicular to the coast and paralel to each other, approximately separated by 50 meters. The areas enclosed beweeen the transects were names A, B, C and D. We considered nine traits reportedly correlated to light and inorganic nutrients preemption, namely, leaf maximum length (cm), leaf maximum width (cm), vertical rhizome length (cm), leaves per shoot, rhizome diameter (cm), roots per meter, root maximum length (cm), leaf mass area (grams per square centimeter), and shoots per meter. To quantify the seagrass traits at each site/sampling event, we defined four zones of ~2500 m2 per site/sampling event, within which we sampled five ramets (defined as a train of at least two shoots) per species, amounting to a total of approximately 20 ramets per species and site/sampling event. The ramets were transported frozen at -4°C to the Leibniz Centre for Tropical Marine Research for trait measuring. We measured rhizome diameter and root maximum length with a ruler to the nearest millimeter. Number of shoots and number of roots were visually counted, and divided by the length of the ramet.